History Of Indonesian Citizenship Reviewed From Legal And Social Aspects - Aulia, Bunga; Triana, Nur Wira; Br. Perangin-angin, Reh Bungana; Setiawan, Deny (Jurnal Ilmu Sosial Mamangan, 2025)
This research aims to analyze the history of Indonesian citizenship from a legal and social perspective, focusing on the evolution of citizenship law from the colonial period to the implementation of Law No. 12 Year 2006. The main problem raised is the inequality produced by the citizenship system in the colonial period, which creates a hierarchy between European citizens and indigenous people, as well as the challenges faced in the implementation of the latest laws. The research method used is a historical approach that includes the stages of heuristics, criticism, interpretation, and historiography, as well as qualitative analysis of secondary data from legal documents, related literature, and case studies. Research results show that although there is progress in the principles of citizenship that are more inclusive after independence, as reflected in Law No. 62 Year 1958 and changes in the 1945 Constitution, significant challenges remain in the implementation of Law No. 12 Year 2006. This research reveals that although there are efforts to eliminate discrimination, there are still social gaps that need to be overcome. The conclusion of this study emphasizes the need for policy reform to improve justice and social integration in the Indonesian citizenship system, as well as providing recommendations for further research in the field of citizenship history.